PRL2 Controls Phagocyte Bactericidal Activity by Sensing and Regulating ROS - Yin, Cennan; Wu, Chenyun; Du, Xinyue; Fang, Yan; Pu, Juebiao; Wu, Jianhua; Tang, Lili; Zhao, Wei; Weng, Yongqiang; Guo, Xiaokui; Chen, Guangjie; Wang, Zhaojun (Frontiers in Immunology, 2018)
Although it is well recognized that inflammation enhances leukocyte bactericidal activity, the underlying mechanisms are not clear. Here we report that PRL2 is sensitive to oxidative stress at inflamed sites. Reduced PRL2 in phagocytes causes increased respiratory burst activity and enhances phagocyte bactericidal activity. PRL2 (Phosphatase Regenerating Liver 2) is highly expressed in resting immune cells, but is markedly downregulated by inflammation. In vitro experiments showed that PRL2 was sensitive to hydrogen peroxide (H2O2), a common damage signal at inflamed sites. In response to infection, PRL2 knockout (KO) phagocytes were hyper activated, produced more reactive oxygen species (ROS) and exhibited enhanced bactericidal activity. Mice with PRL2 deficiency in the myeloid cell compartment were resistant to lethal listeria infection and cleared the bacteria more rapidly and effectively. Moreover, in vitro experiments demonstrated that PRL2 binds to GTPase Rac and regulates ROS production. Rac GTPases were more active in PRL2 knockout (KO) phagocytes than in wild type cells after bacterium infection. Our findings indicate that PRL2 senses ROS at inflamed sites and regulates ROS production in phagocytes. This positive feedback mechanism promotes bactericidal activity of phagocytes and may play an important role in innate anti-bacterial immunity.